1998
DOI: 10.1590/s1413-81231998000200009
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversidade: o enfoque interdisciplinar brasileiro

Abstract: (Beardsley, 1994). Our efforts aim to provide a secure theoretical basis for the elucidation of this "most marvellous mystery of life, the means by which so much diversity was generated from so little physical material" (Wilson, 1992). After all, "how can you carry out a national policy -or even make intelligent decisions on your own life -if you do not understand the underlying questions" (Sagan, 1996)? This is a genuine Brazilian problem requiring an urgent gathering of efforts, since it has direct practical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
13

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 11 publications
(9 reference statements)
0
6
0
13
Order By: Relevance
“…benzylisoquinolines of increasing oxidation value vs lower WI, i.e. higher HI, of Magnoliidae families) (Gottlieb 1982, 1989, Gottlieb et al 1995b, 1996b. True, gradual oxidation of natural products is a powerful evolutionary phytochemical marker.…”
Section: Are Natural Products and Evolution Connected?mentioning
confidence: 99%
See 1 more Smart Citation
“…benzylisoquinolines of increasing oxidation value vs lower WI, i.e. higher HI, of Magnoliidae families) (Gottlieb 1982, 1989, Gottlieb et al 1995b, 1996b. True, gradual oxidation of natural products is a powerful evolutionary phytochemical marker.…”
Section: Are Natural Products and Evolution Connected?mentioning
confidence: 99%
“…The appropriate methodology, described in our previous articles (Gottlieb 1989, 1990, Gottlieb et al 1995b, Gottlieb & Borin 1997b and books (Gottlieb 1982, Gottlieb et al 1996b) on quantitative chemical biology, replaces the traditional descriptive approach. "If you know a thing only qualitatively, you know it no more than vaguely.…”
mentioning
confidence: 99%
“…4 Previous studies have shown that these glycoalkaloids display antifungical, 5,6 schistosomicidal, 7 antiprotozoal, 8 molluscicidal, 9 antiviral, 10 antimutagenic, 11 and antineoplasic activities against a variety of neoplastic cell lines, [12][13][14] as well as hypoglycemic and gastric emptying inhibitory activities. 15 As stated by Gottlieb and collaborators, 16 Brazilian biodiversity is an important source of wealth, and its benefits do not only depend on the use of biodiversity, but also in its sustainability for proper economic exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…Os estudos Etnobotânicos também se destacam como sendo relevantes para popularização da ciência, valorização da economia, benefícios à sociedade e para conservação da vegetação em diversas regiões brasileiras [3]. O estudo das plantas medicinais é importante para registro de informação, na identificação de espécies e no avanço econômico e de uso medicinal das plantas [4].…”
Section: Introductionunclassified